Growth, development, productivity and post-harvest losses of onion due to pruning during the production of seedlings (Revista de Ciências Agroveterinárias, 2013)
The performance of one or more pruning in the bed (seedlings stage) with view to the conditioning of the onion seedlings and transplanting at the most opportune time is a practice commonly used by the Santa Catarina onion producers in the Alto Vale do Itajaí region. There are no specific studies on the behavior of plants on the practice of pruning. In this sense, this paper aimed to study the influence of aerial pruning of onion seedlings in the bed in relation to the growth and development of the seedlings, plants after their transplant, productivity and storage of bulbs. The treatments were: no pruning (Control), a pruning - done at 55 days after (DAS), two pruning - made 55 and 62 DAS, three pruning - performed at 55, 62 and 69 DAS. We used the experimental design of randomized blocks with four replications. In the initial growth period the experimental plots were formed by beds with 6.0 m2 (1 x 6 m) and floor area of 4.64 m2. In post-transplant phase, we adopted a factorial scheme 4 x 7 and 4 x 4, factors relating to management of pruning of the seedlings and observation dates. We evaluated the number of leaves, dry and fresh biomass of seedlings and plants after transplantation, as well as productivity losses after four months storage of the bulbs. The results indicate the feasibility of pruning the seedling stage with a view to their conditioning and transplant seedlings in the most appropriate time with no reduction in productivity and no increase in post-harvest losses.
Keywords: Allium cepa L.; Conditioning of seedlings; Pruning management; Storage.